Knowledge Engineering and Semantic Web 6th International Conference, KESW 2015, Moscow, Russia, September 30 - October 2, 2015, Proceedings - Klinov, Pavel; Mouromtsev, Dmitry (Communications in Computer and Information Science,, 2015)
This book constitutes the refereed proceedings of the 6th Conference on Knowledge Engineering and the Semantic Web, KESW 2015, held in Moscow, Russia, in September/October 2015. The 17 revised full papers presented together with 6 short system descriptions were carefully reviewed and selected from 35 submissions. The papers address research issues related to semantic web, linked data, ontologies, natural language processing, knowledge representation.